Pawning n00bs: Insights into perceptions of brand extensions of the video game industry. Issue 3 (August 2017) - Butcher, Luke; Tang, Ysobel; Phau, Ian
Highlights: Consumption of video game brand extension by gamers is examined. Contextual information on segmentation of gamers, identity, and elitism are revealed. The extension of Twitch illustrates the value of the community with which the video gaming sub-culture broadly participates in. Abstract: This paper examines gamers' perceptions of video game brand extensions through a grounded-theory qualitative methodology. Results of the focus groups and interviews reveal deep and highly contextual information pertaining to gamer characteristics (discernment and fanaticism) and extension characteristics (affordability, collectability, fit, identity-projection, and ownership), as well as the moderating roles of marketing effectiveness, interpersonal influences, and inelasticity of demand on gaming brand equity. Results provide substantial academic value and deeper insights into this culturally and economically significant industry, with distinct implications for product design, consumer segmentation, and promotion. Chinese Abstract: 本文研究了视频游戏品牌扩张的消费，并揭示了关于游戏玩家、身份和精英各细分市场的有前后关系的信息，这种信息可能是这个新兴的娱乐巨头产业"游戏玩家"决策的驱动因素。具体地说，它在设法回答三个问题，即：（a）游戏社区如何认识视频游戏的品牌扩张？（b）哪些特点促使他们接受？以及（c）游戏玩家对身份的认知如何影响消费习惯？研究结果为这个在文化和经济方面意义重大的产业提供了重大的学术价值和更为深刻的见解。研究结果还通过广告、社交媒体、内容营销、赞助和代言、活动以及更多的沟通策略对传播产生了显著的影响。